A strongly luminescent copper (I) coordination complex with near-unity quantum efficiency. (21st September 2020) - Xu, Chanchan; Lu, Lu; Lv, Le; Li, Yuzhe; Lin, Fang; Yang, Yunxu; Lin, Feng; Luo, Chaoyun; Luo, Dawei; Liu, Wei
Abstract: Single crystals of a zero-dimensional (0 D) copper (I) complex 0 D-CuBr(3-picoline)3 (1 ) has prepared at room temperature. Each molecule of 1 contains one copper ion, which coordinates to three organic ligands and one Br anion. The strong metal-to-ligand charge transfer (MLCT) along with the halide-to-metal charge transfer (XLCT) makes 1 an extremely strong green emitter with near-unity quantum efficiency, exhibiting potential application as lighting materials. Single crystals of a new zero-dimensional (0D) copper (I) complex 0D-CuBr(3-picoline)3 has prepared at room temperature. It serves as an extremely strong green-yellow emitter with near unity quantum efficiency, exhibiting potential application as lighting materials.